2021
DOI: 10.1037/cdp0000442
|View full text |Cite
|
Sign up to set email alerts
|

Internalizing symptoms, intersectional discrimination, and social support among Asian–Pacific Islander sexual and gender minority adults.

Abstract: Objective: This study examined associations of discrimination, social support, and their interaction, with internalizing symptoms among Asian-Pacific Islander (API) sexual and gender minority (SGM) adults in the U.S. Method: Analyses included data from 544 participants who completed an online survey, including measures of three internalizing symptoms (anxiety, depression, and somatization), five forms of discrimination (racism, heterosexism/cisgenderism, and three forms of intersectional discrimination), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…To comprehensively measure different types of direct discrimination, two measures were used. The Subtle and Blatant Racism Scale for Asian American College Students (SABR-A; Yoo et al, 2010) was developed specifically for Asian Americans and has been found to be associated with anxiety and depression (Takeda et al, 2021). The PEDQ-CV (Brondolo et al, 2005) was developed for use across ethnic groups, validated in a multiethnic Asian sample, and has been found to be associated with anxiety and depression (Kwok et al, 2011).…”
Section: Erdmentioning
confidence: 99%
“…To comprehensively measure different types of direct discrimination, two measures were used. The Subtle and Blatant Racism Scale for Asian American College Students (SABR-A; Yoo et al, 2010) was developed specifically for Asian Americans and has been found to be associated with anxiety and depression (Takeda et al, 2021). The PEDQ-CV (Brondolo et al, 2005) was developed for use across ethnic groups, validated in a multiethnic Asian sample, and has been found to be associated with anxiety and depression (Kwok et al, 2011).…”
Section: Erdmentioning
confidence: 99%
“…Como se ha podido observar en otras investigaciones, este es un fenómeno también recurrente dentro del colectivo LGTBIQ+ dado que las experiencias de victimización que sufren estas personas no solo ocurren en un entorno en concreto, sino que suelen repetirse en distintos ámbitos y lugares de su vida (Garaigordobil y Larrain, 2020). Asimismo, los resultados indicaron que las sintomatologías interiorizadas descritas en este estudio se asocian positivamente entre ellas, por lo que se concluye que las personas del colectivo tienden a desarrollar síntomas de depresión, ansiedad y estrés a la vez (Takeda, Rosenthal y Arora, 2021). Finalmente, todos los tipos de apoyo social se relacionaron positivamente, señalando que las personas LGTBIQ+ que encuentran apoyo en un entorno es más probable que lo encuentren también en otros contextos (Shiu et al, 2016).…”
Section: Discussionunclassified
“…In reviewing conceptual and methodological considerations for Latinx mental health research, Torres et al (2018) noted that Latina female adolescents made more suicide attempts than Latino male adolescents or non-Latina White girls. Discrimination faced by those with multiple marginalized identities (e.g., someone who is both a woman and Black) is not comprised of mutually exclusive experiences pertaining solely to gender and ethnoracial status respectively; intersectional discrimination is common (Scheim & Bauer, 2019; Takeda et al, 2021). Moreover, it negatively affects the mental health of women within ethnoracial minority populations (Barile et al, 2017; Vines et al, 2017).…”
Section: Barriers To Accessing Mental Health Carementioning
confidence: 99%